Teachers' Awareness and Acquisition of Questioning Strategies: A Case Study - Alpaslan Sahın (Sakarya University Journal of Education)
The importance of teachers' questioning strategy cannot be underestimated due to its widespread usage and pivotal role in teaching and learning regardless of grades and subjects. This qualitative case study design was employed to investigate middle school mathematics teachers' awareness of asking two types of questions, probing and guiding. The study further explores teachers' habits or skills of questioning and their acquisition of this behavior through face-to-face interviews with four middle school mathematics teachers. It was found that teachers were asking questions consciously and purposefully. Also, teachers' answers revealed that why questions require more higher order thinking than how questions. For the second question, several themes emerged indicating how to acquire more effective questioning skills; student teaching or field experiences, watching and observing their colleagues, and workshops. It was also found that the colleges our participants attended did not provide good education for developing questioning skills. Video clips played important roles in reminding teachers what and why they taught. Importance of letting teachers' watch their own teaching's videotape and questioning strategies in teacher trainings was discussed.